"An unusual presentation of a sacral Ewing's sarcoma in a young Syrian female". (June 2021) - Soltany, Amjad; Sulaiman, Ali; Ibraheem, Batoul; Mahmoud, Ala'a; Alshehabi, Zuheir; Saad, Ahmad; Mahfoud, Moufid
Abstract: A primary spinal Ewing sarcoma is extremely rare to be found. To the best of our knowledge, it is the first reported case for bilateral foot drop as a prodromal symptom of sacral Ewing sarcoma. The case, we are presenting, is of an 18-year-old athletic female, who was presented to the emergency department suffering from sudden severe low back pain radiated to the lower limbs, associated with bilateral foot drop and later urinary incontinence. Following the indicated surgery and subsequent histopathology study, we diagnosed this rare type of tumors. In the following article, we are describing the clinical presenting features of this tumor and discussing the clinical aspects. Highlights: Sacral primary Ewing's sarcoma is a rare tumor. Diagnosis of sacral Ewing's sarcoma is quite challenging. Isolated back pain should be investigated widely. Bilateral foot drop may be noticed as a prodromal symptom in sacral Ewing sarcomas.